Rehabilitation of degraded rangelands in Jordan: The effects of mechanized micro water harvesting on hill-slope scale soil water and vegetation dynamics - Strohmeier, S.; Fukai, S.; Haddad, M.; AlNsour, M.; Mudabber, M.; Akimoto, K.; Yamamoto, S.; Evett, S. R.; Oweis, T. (2021)
Overexploitation and climate change accelerates the degradation of Jordan’s arid rangelands. Uncovered and crusted soils increase runoff and erosion and hinder the emergence of native vegetation. Micro water harvesting combined With shrub-seedling plantation has been widely applied to reverse land degradation trends. However, consequential soil water and vegetation dynamics have been rarely assessed, which constrains further out- scaling of the rehabilitation practice to complex environments. In Jordan, an experiment was set up to study the linkages between local rainfall characteristics, soil moisture, and the development of out-planted shrub-seedlings. Soil moisture was recorded at approximately weekly time-interval during the rainy and dry season 2017/2018 using a manually operated soil water sensor. Transect monitoring was pursued up and down the slope across four micro water harvesting pits and the interspaces. Data confirmed a significant soil moisture increase inside the pits - bridging intra-seasonal dry spells and soil water potentially deep-percolated into the karstic bedrock underneath. The study found that the out-planted shrubs’ stem diameter and height predominantly increased during post rainy season when the interspaces dried up while the pits continued providing moisture. The results are promising and contribute to integrated research towards halting land degradation and sustainable agro-pastoral development.